Iron and zinc concentration of native Andean potato cultivars from a human nutrition perspective - Burgos, G.; Amoros, W.; Morote, M.; Stangoulis, James C.R.; Bonierbale, Merideth W. (Wiley, 2007)
The determination of iron (Fe) and zinc (Zn) concentrations in 49 native Andean potato varieties revealed significant genotypic variation. Comparison of mineral concentrations of 37 of these germplasm accessions grown in two highland locations further revealed significant variation due to environments and genotype x environment interaction. Concentrations in raw, peeled tubers ranged from 9 to 37 mg Fe kg<sup(-1)> and 8 to 20 mg Zn kg<sup(-1)> (dry weight) with accessions 703274 and 701165 showing the highest levels of Fe and Zn, respectively, in both locations. Fe and Zn concentrations were significantly and positively correlated on a fresh weight basis in each site. Assessment of Fe and Zn retention during processing revealed no losses due to cooking, and the only significant differences found in iron content of peeled versus unpeeled potatoes could be attributed to contamination with soil iron, as confirmed by elevated levels of aluminium in the samples. The ranges of micronutrient concentrations reported indicate ample genetic diversity that might be exploited in breeding programmes seeking to increase Fe and Zn levels in human diets.